Understanding public trust in information about interim nuclear waste storage: The roles of acceptance, gender, and proximity - Zabirova, Aizhan; Matsunaga, Hitomi; Kashiwazaki, Yuya; Xiao, Xu; Schneider, Thierry; Takamura, Noboru (PloS one, 2025)
Following the accident at the Fukushima Daiichi Nuclear Power Station in March 2011, the Japanese government implemented extensive decontamination and waste management measures, including the establishment of an interim storage facility in Okuma and Futaba. This study aims to analyze residents’ trust in the information provided by the public authorities regarding this facility and to identify factors influencing that trust. A survey was conducted among 1,558 former residents of Tomioka, Okuma, and Futaba who were 18 years or older and held resident cards for one of these towns in both March 2011 and 2024. The questionnaire collected data on demographic variables; intention to return; thoughts on the storage facility; trust in public information; concerns about radiation-related genetic risks and negative perceptions due to the nuclear accident; and mental health status, assessed using the mental component of the SF-8 health survey. The results showed that 57.7% of respondents trusted the information provided by the public authorities regarding the storage facility. Factors significantly associated with trust included their acceptance of the facility, lack of concerns about radiation-related genetic risks, lack of concerns about negative images resulting from the nuclear accident, and good mental health status. A logistic regression analysis indicated that acceptance of the facility and good mental health significantly increased the likelihood of trusting information provided by the public authorities, while concerns about genetic risks and negative images significantly decreased it. These findings underscore the vital importance of recognizing and addressing residents’ concerns about health risks and negative perceptions related to nuclear waste management. By supporting the mental well-being of the community and fostering transparent communication, authorities can build trust and improve the acceptance of waste management facilities. Actively engaging with residents and responding to their worries facilitates the identification of adequate and acceptable recovery efforts after a nuclear accident.